Conducting research under politics and governance cluster of BRAC Institute of Governance and Development - Uddin, Mohammed Misbah (BRAC University, 2017)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Development Management and Practice, 2016.